Linguistic Profile of an 18th Century Transbaikal Military Official: A Reconstruction from Regional Documentation - S. V. Komogortseva; T. Yu. Ignatovich (Научный диалог, 2024)
This article aims to reconstruct the linguistic profile of a military official — Colonel Peter de Sala — through an analysis of the linguistic features found in 18th-century Transbaikal administrative documents. For the first time, this study introduces a linguistic corpus derived from regional archival documents of an administrative nature, including four orders and one decree, into scholarly discourse. The findings presented herein contribute to addressing the pressing academic issue of describing the language of Transbaikal administrative documents and reconstructing the regional speech norms during the era of Russian pioneers and settlers. Furthermore, the results are significant for examining the characteristics of business writing style in regional documentation and in the context of reconstructing historical linguistic profiles within contemporary linguistic personology. The modeling of historical linguistic identity is conducted according to Y. N. Karaulov’s concept of linguistic personality, which encompasses three levels: motivational, linguo-cognitive, and verbal-semantic. The article also presents an original methodology for analyzing the language of regional administrative documents, enabling the recreation of the linguistic profile of an 18th-century historical figure — a military official — who demonstrated the requisite level of written communication skills essential for effective business interactions.